Gastrointestinal Manifestations of Eating Disorders. Issue 5 (November 2016) - Bern, Elana M.; Woods, Elizabeth R.; Rodriguez, Leonel
Abstract : ABSTRACT: Individuals with eating disorders, including anorexia nervosa and bulimia nervosa, may present with a range of gastrointestinal (GI) manifestations. The oral cavity, salivary glands, GI tract, pancreas, and liver can be impacted by nutritional restrictive and binge/purging behaviors. Complications are often reversible with appropriate nutritional therapy. At times, however, the complications in these disorders may be severe, irreversible and even life threatening. Given the often covert nature of eating disorders, the practitioner must be attentive to subtle clues that may indicate their presence. Extensive diagnostic evaluations of the GI manifestations of eating disorders should be used only when nutritional rehabilitation does not remedy the problems.